The Green Synthesis of 2D Copper Nanosheets and Their Light Absorption - Lee, Suhyun (Materials (Basel), 2021)
In this study, a new green synthesis method for two-dimensional (2D) copper nanosheets is developed using methylsulfonylmethane (DMSO(2)). The chemical composition and light absorption of 2D copper nanosheets are also studied. A new green method is mainly to utilize DMSO(2), which is environmentally friendly enough to be considered a food-grade chemical, unlike the conventional method using toxic chemicals, such as ammonia and hydrazine (N(2)H(4)). With a reducing agent, the aggregation of uncertain copper products was produced in the absence of DMSO(2), while 2D copper nanosheets were formed in the presence of DMSO(2). The optimum concentration of DMSO(2) as a surfactant was determined to be 2 M, resulting in large surface areas with regular edges. FTIR spectrum confirmed C–H bonding from DMSO(2) used to synthesize 2D copper nanosheets. The light absorption peak was revealed at 800 nm in the UV–vis spectrum. This proposed new green method not only has a simpler process than the conventional methods, such as hydrothermal method and chemical bath deposition, but also substitutes toxic chemicals with DMSO(2). 2D copper nanosheets can be used for various applications, including conductive filler or ink in the flexible electronics and laser photonics fields.